Peningkatan Kualitas UKM Kuliner Saung Ambu 711 Berbasis E-Commerce Di Desa Cipagalo Kabupaten Bandung - Karniawati, Nia; Adibowo, Rino; Triwahyuni, Dewi; Nurkandias, Muhammad Rizki; Majid, Zidan Raihan; Nur Safitri, Faiza Rahma; Anindia, Haura; Aisy, Alya Rihhadatul (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The purpose of this activity is to improve the quality of e-commerce in Saung Ambu 711 Culinary UKM. E-commerce is selling online. One of the uses of information technology in the economic field or business actors is e-commerce. This PKM partner is a culinary UKM engaged in the productive economy, namely Saung Ambu 711 which is located in Cipagalo Village, Bandung Regency. There are two problems with partners, namely product marketing and business management. The method of implementing PKM activities is carried out with assistance from partners. The results of the implementation of PKM show that there are two problems that exist with partners, the first is a marketing problem, which is overcome by an increase in conventional marketing and digital marketing. The program is carried out with the strength of partner capabilities through e-commerce training. Second, is the problem of business management. This is overcome by providing business management assistance through the purchase of goods that support partner business operations.